1981
DOI: 10.1111/j.1399-3054.1981.tb02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Wall‐protein antibodies as inhibitors of growth and of autolytic reactions of isolated cell wall

Abstract: Antiserum raised against protein prepared from corn (Zea mays L. hybrid B73 X Mo17) seedling cell wall exhibits antigrowth activity and inhibits autolytic reactions of isolated cell wall. The growth of corn coleoptile segments pretreated in wall‐protein antiserum was inhibited 35% compared to tissue which had been exposed to normal serum. Since the cuticle constituted a barrier to the entry of serum protein the coleoptile surface was abraded prior to exposure to the serum. Growth inhibition observed in nonabra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

1986
1986
1996
1996

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 21 publications
1
16
2
Order By: Relevance
“…Plant walls contain numerous hydrolytic enzymes, which have been viewed as catalysts capable of weakening the wall to permit turgor-driven extension (reviewed by Fry, 1988Fry, ,1989. In support of this hypothesis, Huber and Nevins (1981) and lnoue and Nevins (1991) found that antibodies raised against wall proteins could inhibit both auxin-induced growth and wall autolysis of corn coleoptiles. In addition, isolated walls from many species extend irreversibly when placed under tension in acid conditions (Rayle et al, 1970;Hager et al, 1971;Cleland et al, 1987), in a manner consistent with an enzyme-mediated process (Cosgrove, 1989).…”
Section: Introductionmentioning
confidence: 68%
“…Plant walls contain numerous hydrolytic enzymes, which have been viewed as catalysts capable of weakening the wall to permit turgor-driven extension (reviewed by Fry, 1988Fry, ,1989. In support of this hypothesis, Huber and Nevins (1981) and lnoue and Nevins (1991) found that antibodies raised against wall proteins could inhibit both auxin-induced growth and wall autolysis of corn coleoptiles. In addition, isolated walls from many species extend irreversibly when placed under tension in acid conditions (Rayle et al, 1970;Hager et al, 1971;Cleland et al, 1987), in a manner consistent with an enzyme-mediated process (Cosgrove, 1989).…”
Section: Introductionmentioning
confidence: 68%
“…The cause-effect relationship between auxin-induced changes in chemical structure of cell wall polysaccharides and elongation growth has been examined using lectins (4,5), antibodies raised against cell wall polysaccharides (6), and proteins (3,8,11,12,15,22). The results obtained in the present study further confirm the usefulness of antibodies specific for cell wall components for understanding the mechanism by which auxin regulates elongation growth of higher plants.…”
Section: Specificity Of Antibodiesmentioning
confidence: 99%
“…Antibodies were raised in female New Zealand rabbits by administration ofisolated proteins as reported earlier (10,21). Purified exo-and endoglucanases were separately emulsified with Freund's incomplete adjuvant (Difco Labs.)…”
Section: Preparation Of Glucanase Antibodiesmentioning
confidence: 99%
“…The solutions (1-10 AL) containing denatured proteins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) Ag) were applied to a SDS-PAGE slab gel (0.75…”
Section: Sds-page and Western Blots Of Cell Wall Proteinsmentioning
confidence: 99%
See 1 more Smart Citation